Immigrant Adaptation and Acculturation Orientations - Bereza, Monika, 1971- (2010)
The goal of this study was to examine the five acculturation orientations: assimilationism, segregationism, exclusionism, individualism and itegrationism toward Polish immigrants. The Host Community Acculturation Scale was used to measure those orientations. This study also called for research on better understanding of dimensions of Polish culture. Ideas are proposed for better co- operation between immigrants and host members. Results showed with the Icelandic students host majority members that integration and individualism were the preferred orientations, and the least endorsed were assimilation, segregation and exclusionism. The gender variable had no significance at all for the acculturation orientations, but the age variable had a significant difference on the segregation orientation. The attitude toward Polish immigrants was positive/neutral but showed significance difference after the economic crisis and become rather negative. Despite that negative attitude, the host member disagreed to the aspect of immigrants leaving the country, because of the recent economic difficulties. The language skills were the main hindrances for Polish immigrants to overcome in their way for better communication and in general life prospects in Iceland. Other different factors such as religious views, values and behaviors, affected the attitudes of members of the Icelandic host culture towards immigrants from Poland explored the extent. The dimensions of Polish culture strongly represents that Polish society is still, even today characterized by a high power distance and hierarchy level matter. Individualism and masculinity matched perfect with cultural dimensions of Poland but mismatched regards uncertainty avoidance